Safety and Pharmacokinetics (PK) in Humans of Intravenous ETX2514, a β-lactamase Inhibitor (BLI) which Broadly Inhibits Ambler Class A, C, and D β-lactamases. (4th October 2017) - Lickliter, Jason; Lawrence, Kenneth; O'Donnell, John; Isaacs, R
Abstract: Background: ETX2514 is a novel BLI with broad spectrum activity against Ambler class A, C and D β-lactamases. The addition of ETX2514 to sulbactam (SUL) in vitro restores SUL activity against Acinetobacter baumannii; SUL-ETX2514 (ETX2514SUL) MIC90 4 mg/L (>1, 800 globally diverse, recent clinical isolates). ETX2514SUL is under development for the treatment of A. baumannii infections. Methods: A Phase 1, randomized, placebo-controlled trial in 4 parts (15 cohorts) was conducted in 124 healthy subjects to assess the plasma and urine PK of ETX2514 either alone or in combination with SUL and/or imipenem/cilastatin (IMP/CIL): Part A (Cohorts 1–8): ETX2514 single ascending dose (SAD) (0.25–8 g) including an elderly cohort (1 g); Part B (Cohorts 9–12): ETX2514 multiple ascending dose (MAD) (0.25–2 g); Part C (Cohorts 13–14): drug–drug interaction (DDI) between ETX2514 (1 g) with SUL (1 g) and/or IMP/CIL (0.5/0.5 g); Part D (Cohort 15): 11 days of ETX2514SUL (1/1 g) and IMP/CIL (0.5/0.5 g). ETX2514 and SUL were infused over 3 hours (except Cohort 2, 2 hours). Concentrations of ETX2514, SUL, and IMP/CIL were quantified by LC-MS/MS. Non-compartmental  analysis was performed using Phoenix WinNonlin v6.4 to determine PK parameters. Results: Results from Parts A, B, and C are complete (112 subjects; ETX2514:Placebo 84:28). ETX2514 was generally safe and well tolerated either alone or in combination with SUL and/or IMP/CIL; no significant changes in hematology, clinical chemistry, vital signs or ECGs were noted. In SAD, ETX2514 demonstrated linear dose proportional exposure across the dose range with renal excretion as a predominant clearance mechanism. ETX2514 demonstrated lower total clearance and renal clearance in the elderly cohort. In MAD, ETX2514 demonstrated linear dose proportional exposure across the dose range studied with minimal accumulation at Day 8. There was no DDI (either way) between ETX2514 and SUL and/or IMP/CIL. Conclusion: ETX2514, either alone or in combination with SUL and/or IMP/CIL, was generally well tolerated at doses predicted to be clinically efficacious. ETX2514 PK is consistent with a therapeutic dose in the range 0.5–1 g IV q6hour in combination with SUL 1 g. Further evaluation of ETX2514SUL to treat A. baumannii infections is warranted. Disclosures: J. Lickliter, Entasis: Investigator, Funding to conduct the clinical trial; K. Lawrence, Entasis Therapeutics: Employee, Salary. J. O'Donnell, Entasis therapeutics: Employee, Salary; R. Isaacs, Entasis Therapeutics: Employee, Salary.